MENGHIDUPI SPIRITUALITAS PELAYANAN SEBAGAI PUBLIC SERVANT: UPAYA MEMPERSEMPIT RUANG GERAK PERILAKU KORUPTIF DI RUANG PUBLIK - Duli, Lazarus O.; Yustinus, Yustinus (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2023)
The vocation to public service is a vocation whose purpose is to prioritize the public interest. Common welfare is a principle that is always upheld by public servants. The phenomenon of corruptive behavior carried out by public servants that has recently become so widespread has and is undermining the mission of the common welfare. Therefore, the purpose of this study is to uncover the phenomenon of self-enrichment efforts and how the historicity of its journey and try to find what solutions are considered appropriate enough to overcome them. The methodology used in this study is literature research accompanied by a phenomenological approach to the rampant corruptive behavior in public spaces. This study reveals that there is a close relationship between the emergence of the phenomenon of corruptive behavior in life together with the lack of awareness from public servants to live the spirituality of service as public servants. The ideal of becoming a public servant is still only a political jargon to attract the attention and interest of citizens and calm life together in public spaces